Ferromagnetically filled carbon nano-onions: the key role of sulfur in dimensional, structural and electric control - D. Medranda; J. Borowiec; Xiao Zhang; S. Wang; K. Yan; J. Zhang; Y. He; S. Ivaturi; F. S. Boi (Royal Society Open Science, 2018)
A key challenge in the fabrication of ferromagnetically filled carbon nano-onions (CNOs) is the control of their thickness, dimensions and electric properties. Up to now literature works have mainly focused on the encapsulation of different types of ferromagnetic materials including α-Fe, Fe3C, Co, FeCo, FePd3 and others within CNOs. However, no report has yet shown a suitable method for controlling both the number of shells, diameter and electric properties of the produced CNOs. Here, we demonstrate an advanced chemical vapour deposition approach in which the use of small quantities of sulfur during the pyrolysis of ferrocene allows for the control of (i) the diameter of the CNOs, (ii) the number of shells and (iii) the electric properties. We demonstrate the morphological, structural, electric and magnetic properties of these new types of CNOs by using SEM, XRD, TEM, HRTEM, EIS and VSM techniques.